THE EFFECT OF RISK PERCEPTION ON ATTITUDE, SUBJECTIVE NORM, AND INTENTION TO HOARD FOOD DURING THE COVID-19 PANDEMIC IN SURABAYA - Ansell Cohen Harjono; Margaretha Ardhanari (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Intention To Hoard Food Is A Desire When Consumers Try To Engage In Food Hoarding Behavior. Intention To Hoard Food Is A Stage Of Consumer Desire In Determining Their Behavior Before Making An Actual Purchase In A Retail Store. Intention To Hoard Food Can Occur Due To Several Things, Including Attitude And Subjective Norms, Which Are Influenced By Risk Perception. The Purpose Of This Study Was To Determine The Effect Of Risk Perception, Attitude, And Subjective Norm On Intention To Hoard Food Among Retail Consumers In Surabaya. The Population Used In This Study Is Retail Consumers In Surabaya. The Sampling Technique Used Quota Sampling With The Conditions That They Were 17 Years Old And Over And Domiciled In Surabaya. The Number Of Samples Studied Was 130 Consumers. The Exogenous Variable In This Study Is Risk Perception. The Endogenous Variables In This Study Were Attitude, Subjective Norm And Intention To Hoard Food. Furthermore, The Authors Processed The Research Data Using Smartpls 3 To Obtain Significant Conclusions Based On The Research Results. Based On The Calculated Hypothesis Testing, The Results Of This Study, Namely Risk Perception, Can Affect Attitude, Subjective Norm And Intention To Hoard Food. Risk Perception Can Also Influence Intention To Hoard Food Through Attitude And Subjective Norms As Mediators.